A Retrospective Comparative Audit, Investigating the Management of Diabetes Ketoacidosis in two East Midland Hospitals - Jervis, Alex Helen (2012)
Background: One of the main complications of diabetes mellitus is diabetes ketoacidosis (DKA). DKA should be managed following clear written guidelines. However, healthcare professionals do not always adhere strictly to the agreed guidelines and standards. Therefore, there is a need for an audit of current practice. Methods: As an audit has never taken place on the management of DKA, focussing specifically on healthcare professionals’ adherence to protocols, a retrospective audit was carried out on patients’ case notes in two hospitals within the East Midlands, to examine what DKA treatment was implemented and its effectiveness. This method prevents the study outcomes being swayed towards any particular direction because the DKA management has already taken place. As a result of the study it is hoped that the data will highlight other matters of interest, such as whether certain categories of people are more prone to DKA. Results: It was found that different DKA protocols were being implemented in each hospital setting, even though their protocols should have been based on the most up-to-date evidence available. It was also learnt that some healthcare professionals failed to follow the guidelines, and others adapted them. Additionally, Actrapid was the only insulin used for sliding scale insulin, despite inadequate research on the most effective insulin. Furthermore, three groups of people were shown to be ‘at risk’ in this study, and thus more prone to DKA. Conclusion: To improve DKA management and increase the effectiveness and safety of practice for patients, a comprehensive, clear, up-to-date protocol which can be adapted to each patient, along with better designed documentation, needs to be introduced and applied at both hospitals, thus standardising DKA xiii management care throughout hospital settings. Moreover, it is important that when new guidelines and associated documentation are introduced, that healthcare professionals are made aware of them and are trained on their use.